Polymorphism of chromosome 9. Presentation of two cases - Elodia Rivas Álpizar; Ives de la Caridad Otero Pérez; Práxedes Rojas Quintana; Aimé Reyes Pérez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2017)
Polymorphic variants on chromosomes 1, 9, 16, and on the Y chromosome are more frequent in the infertile person than in the general population; the presence of these variants in one or both members of the couple could increase the frequency of idiopathic cause infertility. Chromosome 9 is structurally highly polymorphic and contains the longest region of heterochromatin in humans. For these reasons and because of the indisputable importance of the cytogenetic study in men with severe seminal disorders, as part of the accurate and timely diagnosis of the couple with reproductive failure, the cases of two patients who were treated at the Cienfuegos Regional Center of Assisted Reproduction , for an infertility study. A cytogenetic study was performed and chromosome 9 polymorphism was diagnosed.